Fabrication of TiO2 on porous g-C3N4 by ALD for improved solar-driven hydrogen evolution. Issue 54 (30th August 2018) - Liu, Wei-Szu; Wang, Li-Chen; Chin, Tzu-Kang; Yen, Yin-Cheng; Perng, Tsong-Pyng
Abstract : Schematic of Pt-loaded TiO2 @P-g-C3 N4 2D/2D heterojunction structure and the proposed mechanism of charge transfer for photocatalytic H2 evolution. Abstract : Porous graphitic carbon nitride (P-g-C3 N4 ) thin sheets were fabricated by a one-step calcination of a mixture of urea, melamine, and ammonia chloride at 550 °C. P-g-C3 N4 showed 48% higher photocatalytic H2 production from methanol aqueous solution than conventional urea-derived graphitic carbon nitride (g-C3 N4 ) because the existence of numerous pores reduces the recombination rate of charge carriers. In order to further enhance the photocatalytic activity, TiO2 was uniformly deposited on P-g-C3 N4 by 60–300 cycles of atomic layer deposition (ALD) to form the TiO2 @P-g-C3 N4 composite. They exhibited much higher photocatalytic hydrogen production rates than both TiO2 and P-g-C3 N4 . Among all composites, the sample deposited with 180 ALD cycles of TiO2 showed the highest H2 production because of optimal diffusion length for electrons and holes. It also performed better than the sample of g-C3 N4 deposited with 180 cycles of TiO2 .